P-073 THE MODIFIED SUBLAY TECHNIQUE FOR THE MANAGEMENT OF MAJOR SUBCOSTAL INCISIONAL HERNIA: LONG-TERM FOLLOW-UP RESULTS OF 41 CONSECUTIVE PATIENTS. (13th October 2022) - Zuvela, M; Galun, D; Bogdanovic, A; Bidzic, N; Zivanovic, M; Zuvela, M; Zuvela, M
Abstract: Aim: To present the concept of original technique in the management of major incisional subcostal hernias bassed on sublay position of large haevy-weight polypropylene mesh between the two myofascial layers in the anterolateral abdominal wall. Material and methods: Between January 2010 and May 2022, 41 consecutive patients underwent the modified sublay technique for major incisional subcostal hernia (minimal defect surface100 cm2 or minimal defect width or height 10 cm). The operative technique is: a) hernia sac dissetion and reposition into the abdominal cavity; b) rectus muscle and rectus muscle stump dissection from posterior rectus sheath, rectus muscle atachement dissection from thoracic wall and external oblique muscle dissection from internal oblique muscle around hernia defect at the side of the hernia defect; c) separate posterior and anterior rectus sheaths reconstruction at the midline; d) reconstruction of the posterior miofascial layer suturing internal oblique/transversal muscle and posterior rectus sheaths; e) large haevy-weight polypropilene mesh placement between posterior and anterior miofascial layer; e) reconstruction of the anterior miofascial layer by suturing external oblique muscle and anterior rectus sheaths. Results: A median (range) hernia defect surface was 160 (100–500) cm2. A median operative time was 120 (90–330) minutes. The morbidity rate was 19.5%. A median (range) postoperative hospital stay was 7 (2–24) days. After the median follow-up of 50 (1–124) months, two patients (4, 9%) developed recurrent hernia. Conclusions: The modified sublay technique using large heavyweight polypropylene mesh provides good results in the management of major subcostal abdominal wall defects.